Characterization of the Genetic Program Linked to the Development of Atrial Fibrillation in CREM-IbΔC-X Mice. (August 2017) - Seidl, Matthias D.; Stein, Juliane; Hamer, Sabine; Pluteanu, Florentina; Scholz, Beatrix; Wardelmann, Eva; Huge, Andreas; Witten, Anika; Stoll, Monika; Hammer, Elke; Völker, Uwe; Müller, Frank U.
Abstract : Background—: Reduced expression of genes regulated by the transcription factors CREB/CREM (cAMP response element-binding protein/modulator) is linked to atrial fibrillation (AF) susceptibility in patients. Cardiomyocyte-directed expression of the inhibitory CREM isoform CREM-IbΔC-X in transgenic mice (TG) leads to spontaneous-onset AF preceded by atrial dilatation and conduction abnormalities. Here, we characterized the altered gene program linked to atrial remodeling and development of AF in CREM-TG mice. Methods and Results—: Atria of young (TGy, before AF onset) and old (TGo, after AF onset) TG mice were investigated by mRNA microarray profiling in comparison with age-matched wild-type controls (WTy/WTo). Proteomic alterations were profiled in young mice (8 TGy versus 8 WTy). Annotation of differentially expressed genes revealed distinct differences in biological functions and pathways before and after onset of AF. Alterations in metabolic pathways, some linked to altered peroxisome proliferator–activated receptor signaling, muscle contraction, and ion transport were already present in TGy. Electron microscopy revealed significant loss of sarcomeres and mitochondria and increased collagen and glycogen deposition in TG mice. Alterations in electrophysiological pathways became prominent in TGo, concomitant with altered gene expression of K + -channel subunits and ion channel modulators, relevant in human AF. Conclusions—: The most prominent alterations of the gene program linked to CREM-induced atrial remodeling were identified in the expression of genes related to structure, metabolism, contractility, and electric activity regulation, suggesting that CREM transgenic mice are a valuable experimental model for human AF pathophysiology. Abstract : Supplemental Digital Content is available in the text.